(untitled) (Bioagro, 2021)
In Venezuela there are large areas of soils with the dominance of 2.1 clays with a strong capacity to retain potassium and ammonium ions in the interlaminar clay complex. As the ion K+ and NH4+ have the same oxidation state (valence), as well as a similar ionic radius, both ions can compete in these expansive clays for fixed adsorption sites, and one of them may decrease the binding capacity of the other. Studies carried out on a clay located in Valles del Tuy, Miranda State, indicate the predominance of montmorillonite (bentonite) with a high capacity to fix potassium (Kf), since 54.5 % of K originally added to the soil it was fixed in the interlaminar soil complex. Kf dropped drastically when similar doses of K and ammonium salts (2.0 meq·100 g-1 of NH4Cl and KCl) were simultaneously added to the clay, while at higher doses of NH4Cl in the experimental medium, Kf reached very low values (6 %). These results may indicate that in this kind of soil, a moderately low application of ammonia fertilization may favor the fixation of potassium, which can remain protected from losses due to leaching, therefore, acting as a potential reserve for future plant use.